A case of immune-mediated encephalitis related to daclizumab therapy. (April 2019) - Devlin, Michael; Swayne, Andrew; Newman, Martin; O'Gorman, Cullen; Brown, Helen; Ong, Benjamin; Robertson, Thomas; Airey, Caroline; Blum, Stefan
This report will detail a case of immune-mediated encephalitis in the context of daclizumab therapy. Daclizumab is a humanised monoclonal antibody which, prior to its recent worldwide withdrawal due to safety concerns, was utilised as a disease-modifying therapy in relapsing-remitting multiple sclerosis. The withdrawal of this therapy was prompted by concerns over 12 cases of serious immune-mediated adverse reactions in the central nervous system. We report an additional case, including clinical data and results of neuroimaging, cerebrospinal fluid (CSF) examination and brain biopsy.